Development of functional dietetic snack using black carob flour (Prosopis nigra) and discarded blueberries (Vaccinium corymbosum L.) - Verónica Nancy Miranda; Enzo Goncalvez de Oliveira; Ana Paula Olivares La Madrid; Agustina Marcela Lotufo Haddad; Adriana Noemí Ramón; Fernando Josué Villalva (Revista Española de Nutrición Humana y Dietética, 2022)
Introduction: Snacks have become an important part of the daily diet, however, their nutritional profile could be improved by adding ingredients with health benefits. The aim of this work was to develop a functional dietetic snack using black carob flour and discarded blueberries, and to evaluate its chemical and functional composition.